Challenges and Reflections on Environmental Governance of Short-Video-Driven Outdoor Tourism: A Digital Landscape Perspective - Jia, Hao (International Journal of Natural Resources and Environmental Studies, 2026)
Short-video platforms have reshaped how outdoor tourism is imagined, circulated, and practiced. Through algorithmic recommendation, visual storytelling, and emotional mobilization, natural landscapes are increasingly transformed into digital spectacles that stimulate imitation, destination check-ins, and concentrated flows of visitors. This paper examines the environmental governance challenges generated by this mediated form of outdoor tourism from the perspective of digital landscapes. It argues that ecological risks arise not only from the physical intensity of tourism activities but also from the mismatch between media-driven behavioral diffusion and traditional governance systems. Government regulation remains largely organized around territorial administration, platform responsibility is still insufficiently institutionalized, and public participation is often fragmented and symbolic. To address these problems, the study proposes a collaborative governance framework built around multi-stakeholder coordination, platform accountability, ecological risk early warning, and institutionalized public participation. The findings suggest that environmental governance in the digital era should move beyond post-event administrative control toward data-informed, responsibility-based, and ethically embedded coordination among governments, platforms, social organizations, and users.